Unity in diversity: sculpting Nusantara’s city identity - Lolita, Theresia Lavietha Vivrie; Wuryanta, Aloysius Gonzaga Eka Wenats (Interaksi: Jurnal Ilmu Komunikasi, 2025)
This study examines the development of urban identity in Indonesia's new capital, IKN Nusantara, addressing challenges in environmental sustainability, Indigenous rights, and policy implementation. The research assesses how the city’s planning reflects Indonesia’s cultural and ecological diversity through a qualitative analysis of government reports, academic studies, and news articles. Findings identify three core themes—identity, mobility, and inclusivity—as critical to fostering collective belonging. The study concludes that integrating these elements through participatory governance can establish Nusantara as a model of sustainable urbanism, recommending that the IKN Authority adopt proactive branding strategies to address equity concerns.